Formation of Performing Style in the Context of Piano Preparation of Music Teacher - Maryna Yarova; Valentyn Vovk (Pedagogical Discourse, 2014)
Specific character of music-style phenomenon has been studied in the article, the essence of the notion “performing style» or “loyalty to the style» has been revealed. Specificity of forming music-style conceptions of students of music-pedagogical faculties has been theoretically grounded. That is why, first of all, the teacher should feel and understand the style of the composer for the reliable interpretation of music, he or she should find for it verbal equivalent, in order to help the student to reproduce the style of the performing composition. Thereby formation of the future music teachers the experience of interpretation of music compositions on the basis of the style approach, which is carried out most productive under the conditions of instrumental (in particular piano) preparation of teachers, has become more and more current.